Isolasi dan Penetapan Flavonoid Total Pada Daun Keji Beling (Strobilanthes crispus L.) Menggunakan Metode Spektrofotometri UV-Vis - Moh Rivaldi Mappa; Rizky Resvita R. Bahi; Huwaidah Istiqomah (Journal of Pharmaceutical and Sciences, 2026)
Keji beling (Strobilanthes crispus L.) has several therapeutic activities such as anticancer, antimicrobial, treating diabetes mellitus, cholesterol, and kidney stones. Flavonoids are the main compounds that contribute to the therapeutic activities of keji beling. Along with its therapeutic activities, flavonoids are complicated by physicochemical properties that make these compounds difficult to identify specifically. This study aims to isolate and identify flavonoid compounds in keji beling leaves using UV-Vis spectrophotometry. The method used was experimental, including qualitative and quantitative analysis, with stages including maceration, phytochemical screening, fractionation, thin-layer chromatography (TLC), column chromatography, preparative thin-layer chromatography (PTLC), and UV-Vis spectrophotometry. The extraction results showed a yield of 11.8%. The phytochemical screening test showed positive results for flavonoid compounds. The fractionation process produced two layers, namely polar and nonpolar layers. TLC results with the best solvent ratio (9:1) showed an Rf value of 0.72. Column chromatography provided good separation results. PTC produced blue-white, orange, red, and purple spots. The results of quantitative analysis of total flavonoids using UV-Vis spectrophotometry with quercetin as a standard showed an average of 11.438 mg QE/g extract and a standard deviation (SD) of ± 0.0058 mg QE/g and %RSD of 0.05%, indicating a very good level of method precision with a maximum wavelength of sample absorbance at 433 nm.